URANG KANEKES: A CULTURE ADAPTING TECHNOLOGY - Muhammad Rizky Dhuha (Muhammad Rizky Dhuha, 2023)
The purpose of writing this final project is to find out the Role of the Assistant Director in the Production of the Documentary Film Urang Kanekes: A Culture Adapting, in which this film tells the story of the outer Baduy tribe who live full of local wisdom and slowly begin to adapt to the introduction of modernization into their lives. That is the reason for the writer to make this thesis, apart from the writer's curiosity about the role of an assistant director in producing a documentary film. The final result of making the documentary film Urang Kanekes: A Culture Adapting shows that the outer Baduy tribe actually takes advantage of the influx of modernization in the form of technology and digital media to help their daily lives such as selling online, promoting the Baduy and their crafts through social media, being invited to exhibitions exhibitions in Jakarta as a result of people seeing their artworks or handicrafts being uploaded to social media such as Instagram and Youtube. The author also gains experience and knowledge on how to become a Director of Photography directly, with the responsibilities and burdens that must be borne for the success of this documentary film so that it becomes a useful lesson and knowledge for the writer in the future when he will pursue work in the film field, especially when becoming a Director of Photography.